THE DEVELOPMENT OF DIGITAL BOOK BASED ON CONTEXTUAL LEARNING ON MOMENTUM AND IMPULS AS LEARNING MEDIA OF SENIOR HIGH SCHOOL STUDENTS - NUR KUSUMA, INDRA (Inovasi Pendidikan Fisika, 2017)
This study is intended to describe the development of a digital book based on contextual learning as a media for learning high school students. The results of school identification showed that students had difficulties in physics because it was considered a material contain full of formulas and difficult to understand the concept. This was indicated by the results of Physics teacher’s interviews at SMAN 2 Pare who want to learn based on real-life phenomena. As a solution to the problem, the researcher developed a digital book based on contextual learning. The results of the development are observed from three aspects of feasibility, they are the validity, practicability, and effectiveness of learning media. This project was used R&D method, consist of literature study, field study, product development, validation, revision, trial, analysis, and media product. This study was tested with a sample of 34 students of class X IIS 3 in SMAN 2 Pare. Media validation results showed that this medium is valid with a value of 82.03%. Practicability is reviewed through the implementation and constraints of 90.60%. Effectiveness is reviewed from students learning outcomes of 82.35% and the response of learners showed a very good media response that is equal to 81.62%. So it can be concluded that digital book media based on contextual learning can be used as a medium for students of senior high school.   Keywords: Digital Book, Contextual Learning, Momentum and Impulse, Learning Media.